Assessing and teaching radiotherapy contouring - Duke, Simon L. (2021)
Advanced radiotherapy techniques such as image-guided adaptive brachytherapy for cervical cancer improve local tumour control and reduce treatment toxicity. This benefit is critically dependent on radiotherapy targeting or “contouring” by oncologists. Numerous studies have shown considerable inter-observer contouring variation across all tumour sites, often measured in centimetres, suggesting that current methods of teaching contouring are ineffective. Moreover, assessing contouring competency is currently a subjective, time-consuming and onerous process.